The Principle of Pluriversality in the Indigenous Peoples Recognition Policy - Armansyah; Alwi Alwi; Muh. Tang Abdullah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2025)
This research examines the application of the principle of diversity in the policy of recognizing indigenous peoples in Mamasa Regency, West Sulawesi. This principle offers an alternative perspective to the dominance of single state sovereignty, emphasizing the importance of recognizing the existence of local socio-political systems, including institutional structures and customary law. Using an exploratory case study methodology, this research examines the process of identification, verification, and validation of indigenous communities by the local government. The findings indicate that the policy of recognizing indigenous peoples is normatively quite progressive through the establishment of an Indigenous Peoples Commission. However, its implementation remains hampered by bureaucracy, minimal institutional capacity, and budget constraints. This study emphasizes that respect for diversity is a crucial decolonial step in improving state-indigenous peoples relations. However, political and administrative dynamics remain more dominant than the substance of recognition, resulting in a slow process of restructuring these relations and not yet fully reflecting a commitment to the plurality of knowledge systems and local governance practices